Analysis Motion At The Release Stage of The Javelin Using Kinovea Software - Andri Tria Raharja; Sulaiman Sulaiman; Sri Sumartiningsih; M. E Winarno (International Conference on Science, Education, and Technology, 2022)
The purpose of this research is to analyze the movement in the javelin release stage. The method used in this research is descriptive quantitative. The data taken is the result of analysis using Kinovea software in the form of data on release velocity, angle of release, height of release and angel of attack. The results showed that on the release velocity factor, the first throw obtained a speed of 12.49 m/s while the second throw obtained a speed of 12.87 m/s. The release angle factor shows that the first throw angle is 38 degrees and the second throw is 35 degrees. The factor of the height of the release is that the javelin distance at the time of release is 185.04 cm in the first throw and 186.87 cm in the second throw. The angle of attack factor shows that the angle of the first throw is 3 degrees and the second throw is 2 degrees. The throwing distance shows that the first throw was obtained with a distance of 46.1 m and the second throw with a distance of 47.2 m. The results of the data analysis show that the greater the speed of release and the height of the release, the farther the throw is obtained, while the smaller the angle of release and attack angle, the farther the throw is obtained. Based on this analysis, it is hoped that it can provide a reference to the trainer on how to make good training pattern in achieving achievement.